Implementasi Pendekatan Pembelajaran Mendalam dalam Pembelajaran Pada Konteks Sosial Budaya Untuk Belajar Ketrampilan Berpikir Kritis Siswa SD - Zuni Eka Tiyas Rifayanti; Tasi'awati Salsa Kaliwanovia (Prodi Pendidikan Guru Sekolah Dasar, 2025)
The implementation of PM at every level of education needs to be supported by a conducive learning ecosystem, broad and meaningful learning partnerships, and effective use of digital technology to realize conscious and attentive learning, meaningful and relevant, as well as learning with joy, enthusiasm and passion. From the results of the initial study, it was found that the learning process carried out by teachers still uses traditional learning approaches and methods and the unpreparedness of students to learn. Learning is still dominated by one-way lectures, assessments that rely only on memorization, and other learning processes that do not foster students' creativity and critical thinking skills. This triggers a lack of critical thinking in students in the material presented. Through the implementation of the PM approach, implications for the urgency of harmonization between laws and regulations related to national education standards, curriculum, textbooks, learning processes, and assessments are expected through the application of PM in the Socio-Cultural Context to Develop Critical Thinking Skills of Elementary School Students. This study aims to examine the effectiveness of the implementation of the in-depth learning approach in the context of learning integrated with local socio-culture to develop critical thinking skills of Elementary School students. The background of this research is based on the urgency of developing critical thinking skills at the elementary education level and the need to make learning more relevant and meaningful through an approach that focuses on understanding deep concepts and the context of students' lives. The research method used is descriptive qualitative, which aims to understand phenomena in depth through the collection of descriptive data in the form of written or spoken words from people and observed behavior. The qualitative approach was chosen because it is appropriate to explore the meaning, process, and subjective perspectives of participants on the topic studied. The research was conducted in elementary schools in Surabaya and Sidoarjo. The locations were chosen purposively because they were relevant to the research focus and allowed for in-depth data collection. The subjects in this study were fourth-grade elementary school students. The results of the study indicate that the implementation of an in-depth learning approach that utilizes the socio-cultural context significantly improves students' critical thinking skills, as seen from their ability to analyze information, evaluate arguments, and solve problems related to the surrounding environment. The integration of socio-cultural values in the learning process has also been shown to increase student motivation and engagement. The implications of this research emphasize the importance of adopting a contextual, in-depth learning approach as an innovative strategy to shape a generation that is not only cognitively intelligent but also sensitive to cultural values and capable of critical thinking in facing the challenges of the times.